Pakistan Fights Militant Extremism [Operation Zarb-i-Azb] and the Challenge of Internally Displaced Persons: A Threat to Human Security - Umbreen Javaid (Journal of Political Studies, 2016)
Large- s c a l e internal displacement of the population has persistently haunted the state of Pakistan. It remains one of the important security concerns for the policy-makers. The military operation, Zarb-i-Azb, against militants in the North Waziristan, has created a large number of IDP’s, but there has been a lukewarm response from the concerned authorities in gauging the seriousness of the issue. This paper examines the dynamics of the state engagement with the miserable plight of the IDPs. It also examines the process of rehabilitation and the possible lacunas, which can be addressed to make the entire socio-political effort more fruitful.